2022
DOI: 10.1021/acsomega.1c06283
|View full text |Cite
|
Sign up to set email alerts
|

Natural Nanoclay-Based Silver–Phosphomolybdic Acid Composite with a Dual Antimicrobial Effect

Abstract: The problem of microbial growth on various surfaces has increased concern in society in the context of antibiotic misuse and the spreading of hospital infections. Thus, the development of new, antibiotic-free antibacterial strategies is required to combat bacteria resistant to usual antibiotic treatments. This work reports a new method for producing an antibiotic-free antibacterial halloysite-based nanocomposite with silver nanoparticles and phosphomolybdic acid as biocides, which can be used as components of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Halloysite has been used as a carrier for various antimicrobial agents such as nanoparticles, metal ions, antibiotics, essential oils, biopolymers, phenolic compounds, surfactants and food preservatives. [51][52][53][54] The outer halloysite surface is composed of nonreactive siloxane (Si-O-Si) groups and chemically active Si-OH groups which exist only at the defect areas and edges of the tubes (Fig. 3).…”
Section: Halloysite Based Photoactive Nanomaterialsmentioning
confidence: 99%
“…Halloysite has been used as a carrier for various antimicrobial agents such as nanoparticles, metal ions, antibiotics, essential oils, biopolymers, phenolic compounds, surfactants and food preservatives. [51][52][53][54] The outer halloysite surface is composed of nonreactive siloxane (Si-O-Si) groups and chemically active Si-OH groups which exist only at the defect areas and edges of the tubes (Fig. 3).…”
Section: Halloysite Based Photoactive Nanomaterialsmentioning
confidence: 99%
“…Novikov [93] Ag; PMo Direct antibacterial effect HNT−PMo−Ag Load PMo and then immobilize AgNPs using seed-growth method.…”
Section: E Coli; S Aureusmentioning
confidence: 99%
“…A compendium of studies underscores that distinctly tailored HNT composites wield the capacity for targeted bacterial eradication, [88][89][90][91][92][93][94][95][96][97][98][99][100] with discernible modifiers classifiable into two principal categories: bioactive materials and minerals.…”
Section: Modified Halloysite Nanotubes As Direct Bactericidal Agentmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphomolybdic acid (PMo) was loaded into HNTs to synthesize nanomaterials with bactericidal properties, without the use of antibiotics [ 62 ]. The actual confinement of the PMo inside the tubes was verified by TEM analysis coupled with an EDX probe, and release experiments showed that the total amount of acid loaded in the tubes was released after 135 min.…”
Section: Halloysite Nanotubes Based Antimicrobial Materialsmentioning
confidence: 99%